AN ASSESSMENT OF PHYSICO-CHEMICAL PROPERTIES OF DRINKING WATER SOURCES IN KASHERE, GOMBE STATE - ABU, RAYLEIGH DADA; MICHAEL, GRACE UHWACHE OMETERE; AGBEBAKU, HENRY USIOBAIFO (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2019)
The aim of this study is to examine the quality of drinking water sources available to residential households and the university community in the rapidly growing new federal university town, Kashere. Data was obtained from water samples collected from 11 (eleven) hand-dug wells and boreholes within the vicinity of the university campus and residential dwellings. The samples were analyzed for Temperature, pH, Electrical Conductivity (EC), Turbidity, Colour, Total Dissolved Solids (TDS), Biochemical Oxygen Demand (BOD), Dissolved Oxygen (DO), Magnesium (Mg2+), Chloride (Cl-) and Total Hardness. The results were compared with the standards prescribed by World Health Organization (WHO) and Nigerian Standard for Drinking Water Quality (NSDWQ). With regards to the physicochemical parameters, the results obtained shows that the drinking water sources had a reasonably good chemical quality with the exception of EC, TDS and Mg2+ that were above the WHO and NSDWQ recommended value for drinking water. To improve the taste and aesthetic properties of the water supply, pre-treatment in the forms of boiling, filtration, sedimentation and aeration for up to 1-2 days by households are recommended. Also, good sanitary conditions around the water sources should be encouraged.